Práxedes Mateo Sagasta y Escolar. Estudio y análisis de las características extrínsecas e intrínsecas halladas en la documentación electoral sagastina (1854-1901) ubicada en el Archivo Histórico del Congreso de los Diputados de España - Villarejo Sánchez, Nadia (Revista General de Información y Documentación, 2005)
The subject of the article is based on the parliamentary activity developed by D. Praxedes Mateo- Sagasta y Escolar, parliamentary activity reflected, shaped and conserved, —from half of the S.XIX to principles of the S.XX— in handwritten electoral documents, that they justify all the events of par- liamentary character that happened during the presidency in Spanish Parliament of the investigated deputy.The Historic Archive of the Congress of the Spain Deputies conserves within the Section of Parliamentary Documentation (Series of Electoral Documentation) Sagasta’s electoral documentation (1854/1901), which is conserved in printed format, in the same documentary support in which it was deposited in the moment of its elaboration. For that reason, the objective of the present article is to manifest the intrinsic and extrinsic characteristics found in such documentary collection. Once discovered, studied and/or analyzed these characteristics establish theoretic solutions and in practice immediately, they may eliminate the found deficiencies in the different administrative processes and of classification that has applied on this unique and irreplaceable documentary treasure in the parliamentary history and of the Spanish constitutional law.